2016
DOI: 10.1007/s10329-016-0550-2
|View full text |Cite
|
Sign up to set email alerts
|

Demography and reproductive output in langurs of the Western Ghats, India

Abstract: Life history traits evolve such that the reproductive output of an organism is maximized. Demographic characteristics, a consequence of life history traits, indicate the reproductive output per individual in group-living species. Both phylogenetic and ecological factors influence demographic traits. In the forests of the Western Ghats, India, we studied the demography of three langur species: Semnopithecus johnii, a wet forest-dwelling species; Semnopithecus hypoleucos, largely a wet forest-dwelling species; a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 38 publications
0
6
0
Order By: Relevance
“…By contrast, the present results of activity budgets are not conclusive on whether there is within-group scramble competition in Nilgiri langurs and black-footed grey langurs. It has been observed that black-footed grey langur group size varied between different forest types [Singh Erinjery/Kavana/Singh et al, 2016]. A good percentage of fruit in their diet also indicates that they might experience within-group scramble competition.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…By contrast, the present results of activity budgets are not conclusive on whether there is within-group scramble competition in Nilgiri langurs and black-footed grey langurs. It has been observed that black-footed grey langur group size varied between different forest types [Singh Erinjery/Kavana/Singh et al, 2016]. A good percentage of fruit in their diet also indicates that they might experience within-group scramble competition.…”
Section: Discussionmentioning
confidence: 99%
“…Although it has been found that Nilgiri langurs specialize on young leaves, no evidence suggests that there is within-group competition in the group. Previous studies have shown that Nilgiri langurs and blackfooted grey langurs inhabiting rain forests have small home ranges, small group sizes, and do not need to forage or travel long distances to acquire food [Sushma et al, 2014;Kavana et al, 2015;Singh et al, 2016]. This was probably because of their high degree of folivory which limits the time for other activities [Kavana et al, 2015;Singh et al, 2016].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Earlier, the occurrence of Nilgiri langur was not clear from the Wayanad plateau, Palghat Hills, Nelliyampathi Hills, Cardamom Hills, High Wavy Mountains to Varushanad. However, recent studies confirm their occurrence in those hills (Kavana et al, 2014;Kumara et al, 2014;Kumara & Singh, 2004a;Ram, 2007;Singh et al, 2016) except for the Palghat gap where they are absent. This gap of 41 km in the Western Ghats appears to be a major biogeographic barrier Hunting in many of these regions also further affected the remnant populations of Nilgiri langur (Kumara & Singh, 2004b;Oates, 1979;Pillay et al, 2011).…”
Section: F I G U R Ementioning
confidence: 93%
“…Keywords: Birth rate, demography, group size, population dynamics. DEMOGRAPHIC characteristics are the evolutionary consequences of life history traits which fix in a population as they maximize individual reproductive output [1][2][3] . Demographic characteristics including group size, age and sex composition of the group, birth rate, mortality, migration frequency of individuals, and growth rate, change over time due to ecological constraints 4 .…”
mentioning
confidence: 99%